Agency in the Peripheries of Language Revitalisation : Examining European Practices on the Ground - Mary S. Linn; Alejandro Dayán-Fernández (Multilingual Matters, 2024)
A unique focus on the issue of agency in minority language revitalisation in Europe. This book addresses the question of agency in the revitalisation of minoritised languages in Europe, with each chapter presenting an ethnographic account of how language policy operates in a specific linguistic context. The chapters investigate how grassroots actors shape revitalisation, and how individuals and groups negotiate historical factors, motivations, and institutionalised initiatives and policies in a variety of efforts. Between them the chapters address both contexts where social actors have gained and exerted agency in their revitalisation efforts, and contexts where issues of authority, authenticity and lack of engagement plague efforts; these chapters provide insights into how social actors work within and against social conventions and strictures. This book is available Open Access under a CC BY ND License.